Contributions of Evolutionary Psychology and Behavior Analysis About Jealousy (Brazilian Journal of Behavioral and Cognitive Therapy, 2005)
Studies about jealousy present several controversies, including the very definition of the phenomenon. Thus, being a present-day and frequent question in the clinical context, it is necessary to discuss about important aspects that should guide the professional's performance when dealing with the complaint of jealousy. This is the central aim of this paper and it will be based on the propositions of Evolutionary Psychology and Behavior Analysis. While the former understands the jealousy as an adaptative response whose function would be preserving a relationship threatened by sexual treachery and consequently necessary to the relationships, the latter proposes that the jealousy could be seen as a negative emotion or, since every behavior has a survival value, as an adaptative one, but it is not considered necessary to the relationships even if it is an expected and culturally reinforced pattern. The differences between these theories have implications to the clinical intervention and they deserve a discussion.